2004
DOI: 10.2486/indhealth.42.124
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Research in Taiwan.

Abstract: This article gave a brief introduction of population, labor force, general status of occupational safety and health in Taiwan. Statistics of occupational injuries and health disorders, laws and regulations relevant to occupational health were also covered. Research activities driven by universities, research institutes, society/association were provided. Two multi-lateral collaborative research examples were presented: an intoxication outbreak-initiated CS 2 study and an informationdemand-motivated 2-methoxy-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The major law relevant to occupational safety and health in Taiwan is the Labor Safety and Health Act, which was promulgated in 1974 and amended in 1991. This law was enacted to prevent occupational accidents and improve labor safety and health (Shih et al, 2004). The Act requires employers to report any fatal occupational injuries to the appropriate inspection agency within 24 h. Trained inspectors must then inspect the workplace and file a formal accident report to the Council of Labor Affairs.…”
Section: Methodsmentioning
confidence: 99%
“…The major law relevant to occupational safety and health in Taiwan is the Labor Safety and Health Act, which was promulgated in 1974 and amended in 1991. This law was enacted to prevent occupational accidents and improve labor safety and health (Shih et al, 2004). The Act requires employers to report any fatal occupational injuries to the appropriate inspection agency within 24 h. Trained inspectors must then inspect the workplace and file a formal accident report to the Council of Labor Affairs.…”
Section: Methodsmentioning
confidence: 99%
“…Nineteen of them were considered as pertinent. These articles were divided into case series or specific workplace experiences (Bernacki and Tsai 1996;Dellestable and Gaucher 1998;Duscio et al 2003;Placidi et al 2002;Sallie and McDonald 1996), epidemiological studies (Chau et al 2004a, b, c;Gauchard et al 2003), reviews on specific topics (Mangili 2004;Mariotti 2004), methodological aspects (Howard 2002;Iavicoli et al 2002;Krute and Kennedy 1982;McCunney 1996;Schlegel and Weickhardt 1978;Shih et al 2004;Soleo et al 2002) and 1 abstract book (Various Authors 2003).…”
Section: General Framework In Oi Preventionmentioning
confidence: 99%
“…Although there is a small percentage of the workforce working in mining among the industries in Taiwan (less than 1% of the total labor force), [16] the incidence of combined occupational lung diseases and TB was not much less than that in other countries with higher prevalences of occupational lung diseases. [17,18] A systematic analysis of 2001 to 2011 studies revealed that the pooled rate of coal workers’ pneumoconiosis patients combined with TB was 10.82%.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Taiwanese public health officials are concerned about chronic lung injury due to occupationally inhaled particulate toxins. [16] Furthermore, data from the Department of Labor Insurance Statistics show that pneumoconiosis contributed to the majority of hospitalizations lasting over 4 days, permanent disability, and deaths from occupational disease in Taiwan from 1999 to 2003. [16] Ongoing inflammatory effects from toxic particles retained in airways, even after exposure ceases, result in irreversible biological and functional abnormalities.…”
Section: Discussionmentioning
confidence: 99%